2019
DOI: 10.1590/rbz4820170257
|View full text |Cite
|
Sign up to set email alerts
|

The use of guava byproduct in the production of feedlot sheep in Brazil: impacts on the productive and economic performance

Abstract: This study evaluated the effects of replacing ground corn with dehydrated guava (Psidium guajava L.) byproduct, at concentrations of 0.0, 8.2, 16.4, and 24.6% on the intake and digestibility of nutrients as well as on productive and economic performance of lambs. The study included 40 uncastrated feedlot Santa Inês sheep with an average age of 120 days and an average initial weight of 17.4±1.27 kg, distributed in individual stalls in a completely randomized design with four treatments and 10 replicates. Santa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Thus, in view of the economical results, the inclusion of 40% TP is the best option without affecting the animals health and improving milk production. As occurred in our study, Costa et al [6] evaluated the use of guava agro-industrial by-product in the feed of confined sheep and observed that the inclusion of the by-product led to a reduction in feed costs.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Thus, in view of the economical results, the inclusion of 40% TP is the best option without affecting the animals health and improving milk production. As occurred in our study, Costa et al [6] evaluated the use of guava agro-industrial by-product in the feed of confined sheep and observed that the inclusion of the by-product led to a reduction in feed costs.…”
Section: Discussionsupporting
confidence: 61%
“…In recent years, the cost of concentrate used in animals feed has steadily increased, making the intensive farming systems more expensive [1]. The agricultural wastes and agro-industrial by-products of local origin are gaining renewed interest as alternatives to reduce feeding costs of ruminants [2,3], without changing the yield and quality of products of animal origin [4][5][6]. Additionally, environmental issues associated with both livestock production and by-products accumulation could be prevented [7].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding by-products with energy values, the replacement of corn with guava by-products was indicated to be included in the diet of sheep in confinement ( 84 ). Also, fats and oils have been used in ruminant feed to increase the energy density of the diet.…”
Section: Discussionmentioning
confidence: 99%